2022
DOI: 10.3390/ma15062174
|View full text |Cite
|
Sign up to set email alerts
|

Colour Change of Sustainable Concrete Containing Waste Ceramic and Hybrid Fibre: Effect of Temperature

Abstract: Construction and demolition (C&D) waste was considered as zero value materials and, as a result, most C&D waste materials ended up in landfills, eventually constituting environmental issues. Therefore, it is important to explore the potential of such C&D waste materials for concrete production. Thus, this research effort aims to find a new method to improve sustainable concrete properties exposed to elevated temperatures at the lowest costs and identify the relationship between temperature change a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Tensile strength decreases as elevated temperature increases at any elevated temperature level ( Figure 20 ). All predicted TS values obtained by the ANN model for all temperatures in this analysis are within the range which is nearly identical to other experimental studies conducted by several researchers, [ 43 , 44 ]. The tensile strength of concrete had remained within an acceptable range (as per IS code).…”
Section: Machine Learning Modelssupporting
confidence: 88%
“…Tensile strength decreases as elevated temperature increases at any elevated temperature level ( Figure 20 ). All predicted TS values obtained by the ANN model for all temperatures in this analysis are within the range which is nearly identical to other experimental studies conducted by several researchers, [ 43 , 44 ]. The tensile strength of concrete had remained within an acceptable range (as per IS code).…”
Section: Machine Learning Modelssupporting
confidence: 88%
“…The accuracy of semi-direct UPV is relatively lower. (5) The ratio between surface velocity and direct velocity can be used to determine the dynamic modulus of elasticity and Poisson's ratio of the concrete. If the fibre content increases, the dynamic elastic modulus increases, and the Poisson's ratio decrease for the same length of steel fibre.…”
Section: Discussionmentioning
confidence: 99%
“…(4) Different steel fibre lengths and fibre types should be explored in UPV tests as there are various types available and applied in real concrete structures. (5) To increase the confidence level of UPV to measure the properties of FRC, fibre content could be decided more widely and also matched with real applications. 0.25%, 0.5%, 0.75%, 1% and 1.25% steel fibre content.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the relationship between reflection loss and compressive strength is independent of curing temperature. Najm et al [ 25 , 26 ] studied the colour and strength change of the sustainable concrete containing waste ceramic and hybrid fibre in ambient and elevated temperatures. It was found that the appearance of colour alteration usually coincided with the onset of a significant strength loss due to elected temperatures.…”
Section: Introductionmentioning
confidence: 99%